Impact of salinity and carbonate saturation on stable Sr isotopes (δ88/86Sr) in a lagoon-estuarine system. (15th January 2021) - Shao, Yuexiao; Farkaš, Juraj; Mosley, Luke; Tyler, Jonathan; Wong, Henri; Chamberlayne, Briony; Raven, Mark; Samanta, Moneesha; Holmden, Chris; Gillanders, Bronwyn M.; Kolevica, Ana; Eisenhauer, Anton
Abstract: Local carbonate cycling in lagoon-estuarine systems, involving processes such as inorganic and biogenic carbonate precipitation/dissolution, represents an important but poorly constrained component of the coastal carbon budget. This study investigates the sensitivity of stable Sr isotope tracer (δ 88/86 Sr) with respect to carbonate saturation and salinity of local waters in the Coorong, Lower Lakes and Murray Mouth (CLLMM) estuary in South Australia. The CLLMM has an extensive range of salinity from fresh to hypersaline (from ∼0 to over 100 PSU), with corresponding variations in water chemistry and major ion composition that in turn controls mineral saturation states, and thus CaCO3 precipitation/dissolution in local waters. Here we use the novel δ 88/86 Sr tracer in tandem with the more established radiogenic Sr isotope ratio ( 87 Sr/ 86 Sr), where the latter is a robust proxy for Sr sources and thus water provenance. We also produced a geochemical (PHREEQC) model of calcium carbonate (CaCO3 ) saturation changes across this unique lagoon-estuarine system. The results indicate a systematically increasing trend of δ 88/86 Sr (from ∼0.25‰ to ∼0.45‰) with increasing salinity and CaCO3 (aragonite, calcite) saturation indices of the coastal waters, which in turn suggest an overall control of carbonate dissolution/precipitation processes on the stable Sr isotope composition in the CLLMM system. This was further corroborated by Ca isotope data (δ 44/40 Ca) published previously on the same samples from the Coorong, as well as a quantitative simulation of local carbonate removal in the lagoon based on Rayleigh modelling and Sr isotope data. Overall, our results confirm that a coupled Sr isotope approach (combining 87 Sr/ 86 Sr and δ 88/86 Sr) can be used to constrain not only the main water sources (continental versus marine Sr) but also local CaCO3 dissolution/precipitation processes, and thus inorganic carbon and coastal carbonate cycling in the CLLMM system. Finally, this coupled δ 88/86 Sr and 87 Sr/ 86 Sr approach can be potentially applied to fossil carbonate archives to reconstruct paleo-hydrology and salinity changes in the CLLMM and/or other carbonate-producing coastal systems.